TERAPI HERBAL MINUMAN KUNYIT ASAM UNTUK MENURUNKAN INTENSITAS NYERI DISMENORE PADA REMAJA PUTRI DI PONDOK PESANTREN - Supatmi, Supatmi; Wulandari, Yuanita; Mukarromah, Nur; Yumni, Fathiya Lutfil; Anandhita, Aries Chandra; Husna, Anis Rosyiatul; Priyantini, Diah; Prabawati, Chlara Yunita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Dysmenorrhea, or menstrual pain, is a common health problem that is often experienced by adolescent girls, especially those who live in Islamic boarding schools. Herbal therapy based on local wisdom is important to provide intervention to adolescent girls, turmeric and tamarind drinks have emerged as a very promising alternative and are increasingly popular in the community. Through this approach, it is hoped that adolescent girls can gain a better understanding of dysmenorrhea pain management and obtain safe and effective alternative treatments. The method of implementing community service is carried out first with preparation, implementation, and evaluation. The implementation stage is carried out by providing interactive education about dysmenorrhea, the factors that influence it, and the benefits of turmeric and tamarind as a natural alternative, printing step-by-step instructions for making turmeric and tamarind herbal medicine by involving active participant participation, distributing turmeric and tamarind herbal medicine to participants accompanied by an explanation of its benefits and nutritional content, detailed explanation of the correct way to consume it, the right dosage, and the recommended frequency of use and a question and answer session to clarify questions or concerns of participants regarding the use of turmeric and tamarind herbal medicine. The results showed that the intensity of Dysmenorrhea Pain 80% of participants reported decreasing after consuming turmeric and tamarind drinks regularly. The average decrease in pain intensity was 3 points on a pain scale of 0-10. This shows that dysmenorrhea pain can be reduced with turmeric and tamarind herbal drink therapy.